LEXICAL AND GRAMMATICAL PECULIARITIES OF SCIENTIFIC-TECHNICAL TEXTS: NEW TRENDS - Ігнатюк, О.Г. (SWorldJournal, 2023)
The science of translation and translation theory, or translation studies, is one of the youngest sciences of linguistics. There is an ever-increasing need for communication in fields such as science, culture, trade, etc. in the world. In most cases, this